De keizersweg, een sociale geschiedenis - Randeraad, Nico (Studies over de sociaaleconomische geschiedenis van Limburg, 2022)
The inaugural lecture of the current SHCL Director, Nico Randeraad, delivered on 10 September 2021 in the Aula of Maastricht University, deals with a new focus of the Centre on the ‘social history of landscape’. In his lecture Randeraad zooms in on the ‘Imperial Route’ between Paris and Hamburg, in particular the stretch through the small town of Rekem in Belgium, ten kilometers north of Maastricht. He proposes to regard the road as an entity with agency within a network of people, materials, and natural phenomena. Research along these lines into the past of roads, rivers, canals, pipelines and the like easily interconnects with broader (cross-)regional social histories of infrastructure, economic development, life stories and migration.